Student’s commitments and preferences in online learning - Muhfahroyin Muhfahroyin; Agus Sujarwanta (Intelektual Pustaka Media Utama, 2023)
During the COVID-19 pandemic, the learning was conducted by online system. The objective of the research was to understand the commitments and preferences of students in online learning. A total of 516 students participated in filling out an online questionnaire. The data were analysed descriptively referring to the critical success factors (CSFs). Based on the research result, there were three most dominant obstacles, they were: i) Internet interference (42.71%); ii) Limited quota (24.49%); and iii) Other activities (22.92%). There were students who did not attend full-time (22.45%). The weak commitment was boredom (2.04%) and feeling that they understood the module (5.10%). There were students who do not study full-time, only filling out the attendance list (53.1%). A small number of students (2.04%) fill out the attendance list and upload assignments as a top priority. According to this research, 46.7% of students liked online learning and 39.7% did not like it. In addition, 42.83% of students were bored. It means that about 60% of saturation comes from like-dislike preferences. The remaining 40% are influenced by other factors. The students’ commitments and preferences are influenced by many factors. Those who force themselves to learn ineffectively will be at risk of learning loss.